Ways to Implement Creative Thinking and International Assessment of Teaching (Journal of Pedagogical Inventions and Practices, 2023)
This article provides detailed information and examples of how to implement an innovative teaching method, creative thinking, and international evaluation program, including innovative teaching technologies, methods, methods, and tests.